Pelican - Oželis, Remigijus (Bogoslovni vestnik, 2023)
Alongside with the legendary phoenix, which rises from death through the fire, and with the lamb, which expresses selfless love, the Pelican is one of the oldest symbols of Jesus Christ. This article reviews the rise of the legends about the sacrifice of the pelican, discusses the pelican as a symbol of the sacrifice of Jesus Christ and presents Jesus Christ as a true Pelican, feeding His faithful with His blood. Seeing the pelican through the eyes of the faith helps to discover the deepest Christ’s message: to give oneself to one’s brothers because it will make visible what evangelist John said about Jesus’ love: “Greater love has no one than this: to lay down one’s life for one’s friends.” (Jn 15:13) The symbol of the pelican in Christianity evokes contemplation of the sacrifice of Jesus Christ, understanding the depth of God’s love and gratitude for this sacrificial love. Representation of Jesus’ sacrifice through the symbol of the pelican visually reminds us that the Lord, when He feeds people with His Body, receives them into Himself to become His Body.
Keywords: christianity; Jezus Kristus; krščanstvo; nesebična ljubezen; pelican; pelikan; sacrifice; selfless love; simbol; symbol; žrtvovanje